The Physical and Chemical Air Quality, Worker's Characteristics, and Respiratory Symptoms Among Printing Workers in Surabaya - Devi Anggar Oktaviani; Corie Indria Prasasti (Universitas Airlangga, 2016)
Abstract: Printing industry is an industry which in its production process generate air pollutants such as Particulate Matter (PM). The exceeds limit of PM2,5 can cause respiratory symptoms, cardiovascular disease, and pulmonary function disorder. The objective of this study was to analyze physical and chemical air quality and respiratory symptoms among printing industry workers in Surabaya. It was observational study with cross sectional approach and analyzed descriptively. The physical and chemical air quality was measured by Thermohygrometer and Haz Dust EPAM 5000 at three different areas in production unit. Worker's characteristics and respiratory symptoms were obtained from 20 respondent's questionnaires. The highest concentration of PM2,5 level was at cutting room (area 1), which maximum concentration was 20.0 Î¼g/m3 and the average was 6.1 Î¼g/m3. The result showed that PM2,5 levels was below threshold limit value. It is suggested to printing industry to improve administrative control application by managing work period and useing mask, to clean ventilation, dust collector, or production facilities and to examine health status regularly to public health center for workers at printing industry.Keywords: physical and chemical air quality, printing industry, respiratory symptoms